2014
DOI: 10.15789/2220-7619-2011-1-85-91
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Patients With Oncology Diseases Against Measles and Mumps

Abstract: Резюме. На базе клиники ФГУ НИИДИ ФМБА России обследовано 107 детей (45 девочек и 62 мальчика) в возрасте 20 месяцев-14 лет (9,62±0,37 лет) с острым лимфобластным лейкозом и солидными опухолями в анамнезе. У всех детей изучен прививочный анамнез, определены титры специфических антител к кори, паротиту, иммунный статус. Не защищены и имеют низкие титры против кори в 83,8%, против паротита-в 85,4%. Иммунологическое обследование этих детей уже через 4 месяца после окончания терапии свидетельствует об отсутствии п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the comparison group, which included patients who received booster vaccine but did not receive medication support, the proportion of individuals with undetectable anti-measles antibody titers was 26.9% [ 43 ]. Other authors also reported data suggesting that immune-active agents of various types might improve the production of specific anti-measles antibodies [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison group, which included patients who received booster vaccine but did not receive medication support, the proportion of individuals with undetectable anti-measles antibody titers was 26.9% [ 43 ]. Other authors also reported data suggesting that immune-active agents of various types might improve the production of specific anti-measles antibodies [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%